High-density lipoprotein cholesterol and nasal colonization of Staphylococcus aureus: results from the 2001–2004 National Health and Nutrition Examination Survey (NHANES) - Jingli Wen; Zhenjiang Zhang (BMC Infectious Diseases)
Abstract Background High-density lipoprotein cholesterol (HDL-C) is negatively associated with infectious diseases, but the relationship between HDL-C and nasal colonization of Staphylococcus aureus is unclear. Objective To investigate the relationship between HDL-C and nasal colonization of Staphylococcus aureus. Methods The cross-sectional study included 7731 participants from the 2001–2004 National Health and Nutrition Inspection Survey (NHANES) survey cycle who had complete data. After adjusting demographics and lifestyle, we used multivariate logistic regression to analyze the relationship between HDL-C and nasal colonization of Staphylococcus aureus. We also used restricted cubic splines (RCS) to analyze the nonlinear relationship between HDL-C and nasal colonization of Staphylococcus aureus. All the analyses adjusted the relevant covariates. Results The mean of HDL-C in this study was 1.38 ± 0.64 mmol/L and the colonization rate of nasal colonization of Staphylococcus aureus was 26.2%. Both unadjusted model (OR = 0.71; 95%CI: 0.62–0.80; P < 0.001) and preliminary adjusted model (model 1: OR = 0.77; 95%CI: 0.67–0.89; P < 0.001) showed a significant negative correlation between HDL-C and nasal colonization of Staphylococcus aureus. After adjusting all variables in model 3, the relationship between HDL-C and nasal colonization of Staphylococcus aureus was still significant and negatively correlated (OR = 0.79; 95%CI: 0.69–0.92; P = 0.002). In addition, through RCS analysis, there was also a significant negative correlation between HDL-C and nasal colonization of Staphylococcus aureus (P for non-linear = 0.034). In subgroup analysis, only gender has a significant impact on this relationship (P for interaction = 0.013). In male, for each additional raising unit of HDL-C, the risk of nasal colonization of Staphylococcus aureus decreased by 38% (OR = 0.62, 95%CI: 0.49–0.79); in female, the relationship was no longer significant. We did not observe the interaction between all the other subgroup analysis results (P for interaction > 0.05). Conclusions We found that HDL-C was negatively correlated with nasal colonization of Staphylococcus aureus, especially in male, even after adjusting for various variables. These findings provide valuable insights into the development of early intervention strategies in people at high risk of infectious diseases.